Methods Of Developing Technical Creativity Of Primary School Students (Wire Insights: Journal of Innovation Insights, 2023)
This article describes the role and importance of ways to develop scientific, technical, artistic creativity through the use of new pedagogical technologies such as modulartechnical experiments, morphological analysis, brainstorming, problem situations aimed at developing the level of knowledge, skills and abilities of primary school students